Biomass Production and Nutrient Removal by Switchgrass under Irrigation. (1st January 2015) - Kimura, E.; Collins, H. P.; Fransen, S.
Abstract : Switchgrass ( Panicum virgatum L.) was identified to supply a major portion of U.S. energy needs when used as a fuel. Assessments of the export of essential plant nutrients are needed to determine impacts on soil fertility that will influence fertilizer recommendations since the nutrients contained in the aboveground biomass will be removed from the field when processed as a bioenergy feedstock. The objective of this study was to determine the influence of N fertilization rates (112 and 224 kg N ha −1 yr −1 ) on the biomass production, nutrient removal, and nutrient concentration of switchgrass grown under irrigation in the lower Columbia Basin of the Pacific Northwest (PNW). Aboveground biomass yields averaged over 5 yr of 23.0, 19.9, and 17.7 Mg dry matter (DM) ha −1 yr −1 for Kanlow, Shawnee, and Cave in Rock, respectively. Kanlow cultivar increased biomass yield at the 224 kg N ha −1 rate compared to two upland cultivars. The annual removal of macronutrients from the field averaged 237 kg N ha −1, 37 kg P ha −1, 326 kg K ha −1, 15 kg S ha −1, 68 kg Ca ha −1, and 43 kg Mg ha −1 among cultivars. Switchgrass produced 93 kg of biomass per 1 kg of N. Micronutrients removed at harvest averaged <1 kg ha −1, while Fe removal was 3.4 kg ha −1 . Increased yields and enhanced uptake of essential nutrients especially after reaching stand maturity in the third year resulted in high nutrient removal with the biomass harvest.